Shear Fragility Analysis of Non-Classically Damped Three-Dimensional Structures Under Seismic Excitation - Jinghui Wang; Ping Tan; Tiancan Huang; Xuefeng He; Fulin Zhou (Buildings)
This study proposes a seismic performance evaluation method for structures using the base shear index to calculate the collapse probability. After non-proportional damping was applied to the three-dimensional bar system model, the structural dynamic response was computed through large-scale finite element analysis. A three-dimensional matrix element for calculating viscous dampers was established in this study. The viscous unified elastoplastic (VUEL) damper element program was compiled using the Fortran language into the ABAQUS 6.14 software. An incremental dynamic analysis (IDA) routine was developed using Python 3.0 within the environment of ABAQUS. The uncontrolled structure was designed using the forced decoupling response spectrum method (FD-RSM), while the damped structure was designed using the complex modal response spectrum method (CM-RSM). Seismic fragility analysis was conducted on both uncontrolled and damped structures using the recommended far-field and near-field earthquake records from ATC-63 FEMAP-695. The shear-based fragility index and collapse probability were investigated to comprehensively assess the seismic performance of the uncontrolled and damped structures. The analysis results indicated that the ratios of the limit performance states for moderate damage (IO), severe damage (LS), and complete damage (CP) in the structure were 1:1.6:2.6. Compared with the various limit performance states of the uncontrolled structures, the increments in the moderate, severe, and complete damage limit performance states of the damped structures were 12.79%, 14.86%, and 16.97%, respectively.